Youth Exposure, Engagement, and Impulsive Grassroot Activism in the Digital Political Landscape in Solomon Edebor’s Good Morning, Sodom and Olu Obafemi’s The New Dawn - ABE, Olanipekun Emmanuel; OLADELE, Adeola Temitope (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Youth exposure and engagement in the digital age have significantly helped to shape contemporary socio-political behaviour mirrored through numerous social and political discourses emanating from society. As young individuals increasingly see the need to meet standards raised by contemporary realities, several social engagements affect their behaviour. However, the rise of grassroots activism in the society demands an immediate response considering its socio-political implications. This study examines the socio-political engagement in the society from the lens of Solomon Edebor's Good Morning, Sodom and Olu Obafemi's The New Dawn. Youth engagement reveals widespread social and moral decay permeating modern lifestyles. On the political plane, maladministration is depicted as a repressive force that precipitates rigorous interaction that actively calls for change. The aforementioned are emergent themes that pose issues of discourse in the selected drama texts. This paper engages a sociological theoretical framework to investigate patterns of social and political engagement within society. However, the expansion of youth engagement in social and political activities inherently results in a greater comprehension of complex political issues. This study concludes that the dynamics of political activism are essential for fostering meaningful youth engagement in shaping policies that affect the lives of the citizenry.